The role of universities' sustainability, teachers' wellbeing, and attitudes toward e-learning during COVID-19 - Fülöp, Melinda Timea; Breaz, Teodora Odett; He, Xiaofei; Ionescu, Constantin Aurelian; Cordoş, George Silviu; Stanescu, Sorina Geanina (Frontiers in Public Health, 2022)
In recent years, universities worldwide have experienced rapid changes with an impact, which have been influenced by technological progress and the social trends of digitalization. Like all other revolutionary changes, digital transformation involves intense adjustment/readjustment. University sustainability must be the active involvement of all higher education institutions. Thus, the present research aims to analyse teachers' acceptance of new technologies and the impact on their well-being and university sustainability. In order to achieve our goal, we made a questionnaire based on the literature, and with the help of the technology acceptance model, we tested our hypotheses. The results indicate several dissatisfactions on the part of teachers regarding adapting to new technologies and even a personal discomfort in adapting to these new technologies. Thus, we can note that well-being significantly influences job satisfaction and teachers' involvement in sustainable development.